Technology-mediated task-based language teaching: A qualitative research synthesis - Chong, Sin Wang; Reinders, Hayo (Language learning & technology, 2020)
In the past 10 to 15 years, researchers have begun to explore the possibility of synthesizing research on task-based language teaching (TBLT) and computer-assisted language learning (CALL) in the interests of advancing the development of both fields as well as informing practice. In particular, there has been an increasing number of naturalistic, classroom-based studies, which have demonstrated the affordances of TBLT in particular contexts, but whose findings may be less generalizable. Against this backdrop, a qualitative research synthesis of these classroom-based studies is warranted. The current study adopts grounded theory (GT) as the methodology to systematically synthesize qualitative findings from 16 technology-mediated TBLT studies published between 2002 and 2017 in second and foreign language contexts. This resulted in the identification of (a) the characteristics of technology-mediated TBLT, (b) the affordances and limitations of technology-mediated TBLT, and (c) the factors affecting the effectiveness of technology-mediated TBLT. Following this synthesis, a possible research agenda is proposed and practical implications are suggested.